2010
DOI: 10.2486/indhealth.ms1131
|View full text |Cite
|
Sign up to set email alerts
|

Work-family Conflict in Japan: How Job and Home Demands Affect Psychological Distress

Abstract: The aim of the present study was to examine how job and home demands are related to psychological distress in a sample of Japanese working parents with preschool children (n=196). We expected that job and home demands are partially related to psychological distress through work-to-family conflict (WFC) and family-to-work conflict (FWC), respectively. Structural equation modeling showed that, as expected, home demands were partially related to psychological distress, both directly and indirectly through FWC. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 37 publications
4
25
1
1
Order By: Relevance
“…Also [121] The results showed no total effect of work demand on psychological distress. This finding contradicted the findings in the study of [21] which found that job demand had a significant positive effect on psychological distress. This finding also contradicted [25] who found that work demand can lead to psychological strain in the absence of adequate resources and Job Demand -Control Model which posited that work demands exert considerable stress on workers [26].…”
Section: Discussioncontrasting
confidence: 99%
“…Also [121] The results showed no total effect of work demand on psychological distress. This finding contradicted the findings in the study of [21] which found that job demand had a significant positive effect on psychological distress. This finding also contradicted [25] who found that work demand can lead to psychological strain in the absence of adequate resources and Job Demand -Control Model which posited that work demands exert considerable stress on workers [26].…”
Section: Discussioncontrasting
confidence: 99%
“…Terdapat beberapa hasil penelitian yang mendukung pernyataan bahwa workfamily conflict berpengaruh positif terhadap stres kerja seorang individu yakni : Hammer, et al (2004), dan Shimazu et al (2010). Dalam penelitian Shimazu (2010) menjelaskan bahwa konflik kerja dan konflik keluarga secara bersamaan dapat menganggu atau mempengaruhi secara positif stres kerja.…”
Section: Pengertian Stresunclassified
“…These analyses are of cohort members at 45 years old. This may be a late stage in life for work--family conflict, which may be more acute when for caring for younger dependent children (Shimazu et al, 2010;Seto et al, 2004). Thus our findings may not apply across time periods or to other age groups as people face different issues at different career stages (Bedeian et al, 1988).…”
Section: Strengths and Limitationsmentioning
confidence: 83%
“…Also, prior research regarding work--life conflict has often limited the research population to specific categories or professions ) and many studies are not nationally representative as they are limited to subpopulations (Seto et al, 2004;Shimazu, Bakker, Demerouti & Peeters, 2010;Takeuchi & Yamazaki, 2010;Janzen & Kelly, 2012;Grant--Vallone & Ensher, 2001).…”
Section: Introductionmentioning
confidence: 99%